2023
DOI: 10.3389/fmed.2023.1179783
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue presentation, severity, and related outcomes in a prospective cohort following post-COVID-19 hospitalization in British Columbia, Canada

Abstract: IntroductionIncreasing evidence on long-term health outcomes following SARS CoV-2 infection shows post-viral symptoms can persist for months. These symptoms are often consistent with those of Myalgic Encephalomyelitis or Chronic Fatigue Syndrome (ME/CFS). The aim of the present study was to examine the prevalence and outcome predictors of post-viral fatigue and related symptoms 3- and 6-months following symptom onset.MethodsA prospective cohort of patients hospitalized with Coronavirus disease (COVID-19) (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Previous studies investigating risk factors behind PCED showed conflicting results ( 19 , 55 ). In the present study, we set up a multivariate regression analysis, which disclosed a quite different risk profile between acute-phase dyspnoea and exertional dyspnoea in the post-COVID phase.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies investigating risk factors behind PCED showed conflicting results ( 19 , 55 ). In the present study, we set up a multivariate regression analysis, which disclosed a quite different risk profile between acute-phase dyspnoea and exertional dyspnoea in the post-COVID phase.…”
Section: Discussionmentioning
confidence: 93%